PEMETAAN STAKEHOLDERS DALAM PENETAPAN KEBIJAKAN UANG KULIAH TUNGGAL (UKT) DI UNIVERSITAS RIAU TAHUN 2013 - Ricky Perianto; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The Single Tuition is a policy of central government that implemented in a state university. So that,this research purpose is to knowing what actions will take by the actors who operate also finding what tools and power sources which used in The Single Tuition implementing. The theory which believed relevant to this matter is a Policy Implementation theory by Mirille S. Grindle. This is a describtive research which use a qualitative approach as the analysis tools. The research is conducted in Universitas Riau and take data sample in Badan Kerjasama danPengembangan Universitas Riau. This research use documentations and interviews informanas information`s objects in order to reach the purpose for informations in this research is primary data and secondary, that achieved from documentations and direct interviews to informanin the research.Single Tuition policy is regulated normatively in the Regulation of the Minister of Education and Culture number 53 of 2013 on Tuition Fees Single and Single. Riau University as one of the state university and then apply Tuition single system with the birth of the Decree of the Rector of the University of Riau number 2715 / UN / 19 / TU / 2013. The results showed about not optimal implementation of the Single Tuition Riau University. It looks as determined by the understanding of policy actors Tuition Single in terms of socialization is still limited and the absence of a Standard Operational Procedure (SOP), which is given by the actors involved in the implementation of policies Tuition Single to each Faculty, Department, and Program the study resulted in a Single Tuition policy can not be effective.Keywords: Implementation, Single Tuition, University of Riau.